A critical p-biharmonic system with negative exponents. (1st March 2020) - Sang, Yanbin; Ren, Yan
Abstract: In this paper, we are devoted to the study of critical p -biharmonic system with a parameter λ, which involves strongly-coupled critical nonlinearities and negative exponents. We prove that there exists a positive constant λ ∗ such that the above problem admits at least two solutions if λ ∈ ( 0, λ ∗ ) .